Pontianak city tourism industry as a supporter of conservative attractiveness with environmental insight - Dony Andrasmoro; Novita Sariani (Jurnal Pariwisata Pesona, 2023)
The equator monument is one of the tourism icons of Pontianak City because the location of the tourist attraction is located at 0º of the imaginary line of the equator and is a sign of the boundary of the hemisphere North Latitude and South Latitude. The equator monument has a conservative nuance with environmental insight because the location of the object is associated with the longest river in Indonesia, the Kapuas River which is the lifeblood of the people of West Kalimantan from the social, economic, and cultural sectors. The purpose of this study was to conduct a conservative study of environmental conservation-based tourist attractions. Qualitative-based spatial (geospatial) approach method. The findings of the study show that the approach to the study of environmentally friendly tourism or Sustainable Tourism Development (STD) is environmentally sustainable: A sustainable tourism management model based on ecological balance by considering social, economic, and cultural aspects, so that two zone areas were developed through a weighting assessment of tourism object potential with a value of 164 (high potential) developed through adaptation of STD environmental indicators through the Geographic Information System produced Zone A (main) is the Equator Monument area is a conservative area of geographical value: aspects of physical geography knowledge and Zone B (Supporting) Kapuas River is a hydrological and ecological conservation area zone as one of the ecotourism and hydrological asset-based rivers with an area of about 10 million Ha and has the potential for the endemic habitat of 300 - 500 species of freshwater fish. The two zones encourage the tourism industry of Pontianak City through the management of periodic tourism development (growth-oriented model), increasing tourist attraction through mass tourism attraction (mass tourism) with a model of encouraging sustainable tourism development with environmental and responsible tourism that can be recommended to the Pontianak City Government for sustainable tourism development governance